Tying the Knot with the DēviGender Transgression in Regional and Trans-Regional Discourses - Sarah Merkle (Ksiegarnia Akademicka Publishing, 2021)
The jōgappas are male-born dedicated devotees of the South Indian goddess Reṇukā-Ellamma who adopt feminine characteristics. Due to their devotional practices and gender-specific expression, jōgappas are confronted with and affected by a range of notions on religious hierarchy and gender. They are opposed by cultural agendas in favour of a Sanskritic form of worship, are drawn into urban debates on sexual minorities and become increasingly interlinked with the hijra community. Furthermore, arguments regarding transgenderism in the context of the divine power and aspects of bhakti provide a rhetoric of deification which can be identified as specifically regional. Today, jōgappas face the challenges of negotiating their individual positions and identities within these global, national, urban, trans-regional and regional discourses.